Analisis Model Integrasi Keilmuan Perguruan Tinggi Berbasis Pesantren (From Theory to Practice) - Ibad, Wasilatul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This research is motivated by the dichotomy that has occurred in education in Indonesia. In an effort to overcome this problem, the author presents a concept of knowledge integration. The purpose of this research is to analyze the knowledge integration model of University-based Islamic Boarding School, which focuses on the integration steps that have been implemented by the object of research. The two institutions that became the object of research were the Islamic Institute (IAI) of Al-Khoziny Sidoarjo and the Islamic College of Sabilul Muttaqin (STAIMSAM) Mojokerto. This type of research is field research using a qualitative descriptive approach. It was concluded that the scientific integration developed by the were the Islamic Institute (IAI) of Al-Khoziny Sidoarjo and the Islamic College of Sabilul Muttaqin (STAIMSAM) Mojokerto included a model of knowledge Integration based fiqih. It is called because the emphasis of the idea of integration is more towards Modern knowledge is not technically wrong, but it must be “confirmed” by Islamic values. The ideas developed are practical and strategic. The level of knowledge integration developed by the Islamic Institute (IAI) of Al-Khoziny Sidoarjo and the Islamic College of Sabilul Muttaqin (STAIMSAM) Mojokerto refers to the Connected Model.